(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
The synergy between the state and the market is a key element in creating inclusive and sustainable social welfare. The state acts as a provider of basic services and a regulator to ensure equitable access and social justice, while the market drives innovation, economic growth, and digital transformation. This study employs a qualitative descriptive approach based on literature analysis to examine the relationship between the state, the market, and social welfare policies, focusing on the implementation of the Family Hope Program (PKH) and the National Health Insurance (JKN). The findings reveal that while both programs have positively impacted poverty reduction and improved access to healthcare, challenges such as regional disparities, complex bureaucracy, and protection for informal sector workers remain to be addressed. The National Long-Term Development Plan (RPJPN) 2025–2045 offers strategic opportunities to strengthen state-market synergy through digital transformation, governance enhancement, and public-private collaboration. This article recommends evidence-based policies that focus on reducing regional disparities and enhancing socio-economic inclusion to achieve the vision of Golden Indonesia 2045.